Efek Nefroprotektif Infus Daun Sukun (Artocarpus altilis (Park.) Fsb.) Pada Tikus Jantan yang Diinduksi Karbon Tetraklorida - Cahyaningsih, Rianti Adi; Azizahwati, Azizahwati; Kusmana, Dadang (Majalah Ilmu Kefarmasian, 2011)
Renal dysfunction can be caused by several factors, including hypertension, urinary tract obstruction, autoimmune disorders, urinary tract infection, diabetes mellitus, consumption of drugs that affect nephrotoxic and antibiotic from aminoglycoside class. Breadfruit leaves (Artocarpus altilis (Park.) Fsb.) is a traditional plant that hasbeen used empirically to treat kidney diseases. The research has been done to figure out the nephroprotective effect of breadfruit leaves infusion on white male rats strain Sprague-Dawley previously induced by carbon tetrachloride. There were 25 rats which were divided randomly into five groups. Group I which was the normal control group received CMC 0,5%. Group II which was the carbon tetrachloride control group was induced with carbon tetrachloride that was dissolved in the coconut oil 0,4 mL/kg bw rat. Group III, IV and V were administered doses of infusion 13,5 g/kg bw/day; 27 g/kg bw/day and 54 g/kg bw/day for 7 days. Two hours later, the animals were given carbon tetrachloride induction. At the 8th day, the blood was collected from the orbital sinus and then the rats were performed a surgery to collect the kidney. The urea and creatinine plasma level measurement has been done by colorimetric method and histology of kidney was observed. One way ANOVA (α=0,1) of the study showed that nephroprotective effect of breadfruit leaves infusion were significantly different among groups and dose of 54 g/kg bw/day has the best nephroprotective effect.